Pregunta

Activity 2 Simplify the following WITHOUT the use of a calculator: \( 2.1 \frac{\tan \left(180^{\circ}+x\right) \cdot \cos \left(360^{\circ}-x\right)}{\sin (180-x) \cdot \cos \left(90^{\circ}+x\right)+\cos \left(540^{\circ}+x\right) \cdot \cos (-x)} \)

Ask by Dunn Graham. in South Africa
Feb 27,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The simplified expression is –2.1 sin x.

Solución

We wish to simplify the expression   2.1 · [tan(180° + x) · cos(360° – x)]     ————————————————————————————————————     [sin(180° – x) · cos(90° + x) + cos(540° + x) · cos(–x)] Step 1. Simplify the numerator. • Recall that tan(θ + 180°) = tan θ. Thus,   tan(180° + x) = tan x. • Cosine has period 360°. Also, cos(θ) is even so cos(–x) = cos x. Therefore,   cos(360° – x) = cos(–x) = cos x. So the numerator becomes:   tan x · cos x. Step 2. Simplify the denominator. The denominator has two parts. We simplify each term: Term A: sin(180° – x) · cos(90° + x)   • sin(180° – x) = sin x.   • cos(90° + x) = – sin x     (since cos(90° + θ) = – sin θ). Thus, Term A = sin x · (– sin x) = – sin² x. Term B: cos(540° + x) · cos(–x)   • Notice that 540° = 360° + 180°. Using the periodicity of cosine,     cos(540° + x) = cos(180° + x) = – cos x     (because cos(180° + θ) = – cos θ).   • Also, cos(–x) = cos x. Thus, Term B = (– cos x) · cos x = – cos² x. Adding both terms in the denominator:   Denom = – sin² x – cos² x = – (sin² x + cos² x). Since sin² x + cos² x = 1, we have   Denom = –1. Step 3. Write the simplified expression. The original expression becomes:   2.1 · (tan x · cos x) / (–1) = –2.1 · (tan x · cos x). Step 4. Final simplification. Recall tan x = sin x / cos x. Then:   tan x · cos x = (sin x / cos x) · cos x = sin x. Thus, the entire expression simplifies to:   –2.1 · sin x. Answer: –2.1 sin x.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Extra Insights

To simplify the given expression, we can start by applying some trigonometric identities. 1. **Understanding the Angles**: - \(\tan(180^{\circ} + x) = \tan(x)\) because tangent has a period of \(180^{\circ}\). - \(\cos(360^{\circ} - x) = \cos(x)\) because cosine has a period of \(360^{\circ}\). - \(\sin(180 - x) = \sin(x)\) (sine is positive in the second quadrant). - \(\cos(90^{\circ} + x) = -\sin(x)\). - \(\cos(540^{\circ} + x) = \cos(180^{\circ} + x) = -\cos(x)\) (cosine changes sign). - \(\cos(-x) = \cos(x)\) (cosine is an even function). Now, substituting these identities into the expression gives: \[ 2.1 \frac{\tan(x) \cdot \cos(x)}{\sin(x) \cdot (-\sin(x)) + (-\cos(x)) \cdot \cos(x)} \] This simplifies to: \[ 2.1 \frac{\tan(x) \cdot \cos(x)}{-\sin^2(x) - \cos^2(x)} \] The term \(-\sin^2(x) - \cos^2(x)\) simplifies to \(-1\) (using the Pythagorean identity). This yields: \[ 2.1 \frac{\tan(x) \cdot \cos(x)}{-1} = -2.1 \tan(x) \cdot \cos(x) \] Now, we can utilize the identity \(\tan(x) = \frac{\sin(x)}{\cos(x)}\): Thus, \( -2.1 \tan(x) \cdot \cos(x) = -2.1 \frac{\sin(x)}{\cos(x)} \cdot \cos(x) = -2.1 \sin(x) \). So the final simplified expression is: \[ -2.1 \sin(x) \]

preguntas relacionadas

Latest Trigonometry Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad